The suffix -ee: history, productivity, frequency and violation of stress rules - Ives Trevian (Anglophonia)
According to Bauer (1983), Barker (1998), Plag (2003) and Mühleisen (2010), -ee has become a very productive suffix, not confined any more to its original role in legal language as a patient suffix contrasted with the agent suffix -or (e.g. bailor / bailee). Many new coinages are supposed to have appeared in the 20th century, so that 163 words in -ee are now recorded in the online dictionaries of the OneLook search engine (e.g. American Heritage Dictionary, Cambridge Advanced Learner’s Dictionary, Collins English Dictionary, Merriam Webster’s Dictionary, Oxford Dictionaries, etc.). Some of the words formed with this suffix are now agent instead of patient nouns (e.g. escapee, returnee), occasionally rivalling with other agent suffixes (e.g. signee = signer). Moreover, besides the traditional deverbal formations (e.g. abductee), denominal and even deadjectival coinages are now sanctioned (e.g. asylee, presentee). The purpose of this paper is (1) to show how this historical process came into being, namely when the change occurred from usage in legal language to other uses; (2) to examine this suffix in terms of its morphological productivity, notably to distinguish well-established nouns from mere nonce words, chiefly used as strictly contrastive (e.g. cutter / cuttee, jester / jestee); (3) to ascertain the frequency of -ee suffixed nouns; to do so we have confronted our corpus of -ee nouns with the word frequency search engine Google Books Ngram Viewer and the Collins Dictionary’s Recorded Usage Charts, the former noting the frequency of words since the 16th century and the latter containing dated sentence examples; (4) to determine how many words in -ee violate the rule proscribing two consecutive stresses (e.g. aˌsyˈlee, aˌwarˈdee), this violation being, in principle, allowed only in compound words (e.g. ˈbootˌlegger, ˈteenˌager) or semantically transparent formations with a prefix (e.g. ˌreˈmake, ˌunˈthaw, verbs); an attempt to account for these violations is proposed in this paper, which has inevitably led us to ponder over the impact of this suffix on metrical rules.